Penanggulangan Limbah Ubi Kayu dengan Menggunakan Katalis TiO2/Zeolit Alam Clinoptilolit-Ca secara Sinergi Fotokatalis dan Adsorpsi - Zilfa, Z.; Yusuf, Yulizar; Putri, Alsa Sepia (Jurnal Kimia Unand, 2024)
Cassava waste containing cyanogenic glycosides is very dangerous for the environment because there is cyanide bound to organic compounds. Cyanide bound to organic compounds is degraded by photolysis using TiO2 catalyst/Clinoptilolite-Ca natural zeolite to break the bond between HCN and organic compounds so that it is no longer harmful to the environment, besides that cassava waste also contains suspended solids and organic compounds that affect water quality, resulting in high COD, BOD, TOC, and TSS values in waters. Therefore, the values of COD, BOD, TOC, and TSS were determined before and after degradation. In addition, the effect of time, mass, and type of catalyst (TiO2, Zeolite, and TiO2/Zeolite) on the percentage of cassava waste degradation was also determined. CN- analysis was performed with a UV-VIS spectrophotometer, where maximum absorption occurred at a wavelength of 573 nm. The optimum time of degradation without catalyst is 75 minutes with a degradation percentage of 20.52%, the optimum mass of TiO2/Zeolite catalyst is 0.8 grams with a degradation percentage of 79.97% at 60 minutes, the percentage of degradation using 0.03 grams of TiO2 is 58.65% at 75 minutes, the percentage of degradation using 0.77 zeolite is 35.43% at 75 minutes. COD value before degradation 1406 mg/L and after degradation 465 mg/L. BOD value before degradation 226 mg/L and after degradation 95.4 mg/L. TSS value before degradation 400 mg/L and after degradation 220 mg/L. While the TOC value before degradation was 546 mg/L and after degradation was 670 mg/L. FTIR analysis of cassava waste shows a peak shift indicating degradation, the 750-1000 cm-1 and 1250-1500 cm-1. While the characterization of the TiO2/zeolite catalyst in FTIR and XRD showed no change in the structure of the TiO2/zeolite catalyst before and after degradation.